STRATEGI PEMBINAAN AKHLAK SANTRI DI PONDOK PESANTREN MATHOLI`UL ANWAR LAMONGAN - Ahmad Muhtadi Mahud; Mutiara Sari Dewi; Muhammad Fahmi Hidayatullah (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Moral values or commonly referred to as morals have an important role in the survival of human life in the development of modernization. The phenomenon of the development of modernization has penetrated into religious values which should reflect a good attitude in religious learning. Islamic boarding schools have an important role in the process of moral development for students so that they become human beings with noble character, knowledge, and independence in the daily behavior of students. The intended target is to form and develop the potential of students, so that they become human beings who are knowledgeable, have noble character, and have independence. Through the process of improving morals or good character, respecting spiritual and human values, teaching honest and moral attitudes and behavior. Therefore, the Islamic boarding school is a place to educate and foster students' morals. This phenomenon of moral degradation places Islamic boarding schools as alternatives that need to be studied and used as examples in the study of moral development and improvement. In the process of the success of the pesantren in educating its students, it has basic values. The basic values here are as a form of culture and as a basis for changes that occur in each individual and group. One of the coaching models designed by caregivers and administrators is able to overcome existing problems. It has been proven that the students of the Mathol`iul Anwar Islamic boarding school have achieved various achievements both in the spiritual and academic fields. It is on this basis that encourages researchers to study further with the title